Implementasi Cloud Computing Amazon Web Services (AWS) Pada Web Reservasi Kamar Hotel - Muhammad Syahrul Mubarok; Muhammad Izman Herdiansyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
One of the rapid technological developments currently is information technology. Cloud computing is a client-server concept where resources such as servers, storage, networks, and software are considered as services available to users with the flexibility to be accessed anytime and anywhere. Currently, there are various cloud computing platforms that can be used, and Amazon Web Services (AWS) occupies one of the top positions as one of the largest cloud service providers globally. This advancement makes it easier to access the desired information from various sources, including information about hotel rooms through online searches. This research aims to apply Amazon Web Service (AWS) technology to a hotel booking website. The research method used is action, combined with the Software Development Life Cycle (SDLC) method and literature study. Data was collected from various journals, scientific articles and other online sources. The aim of this research is to utilize Amazon Web Services (AWS) to simplify the process of booking hotel rooms online. By using AWS, access to cloud services is simple, flexible, and fast, with just an internet connection. Migrating websites to the cloud with the help of AWS features can be done faster, easier, and also more cost-efficient. Hopefully the implementation of this online hotel booking service will make it easier for users to get information about hotel rooms and book rooms from various locations.